Understanding the violence and help-seeking experiences of Mi’gmaq women: Qualitative and applied results from a partnered study in the community of Listuguj - Gagnon-Dufresne, Marie-Catherine; Pelland, Danielle; Swasson, Sheila; Isaac, Mitchell; Isaac, Sylvia; Paillé, Isabelle; Dorion-Laurendeau, Mélisande; Cousineau, Marie-Marthe (Alterstice)

(untitled) (Alterstice, 2024)
Indigenous women and girls in Canada are at increased risk of experiencing any type of violence throughout their lives. This pressing public health issue is receiving growing attention as Indigenous communities and others across the country and internationally continue to demand respect for Indigenous women’s human rights to health, safety, and justice. To support their claims, we conducted a five-year partnered study with Indigenous and non-Indigenous non-governmental organizations in the Mi’gmaq community of Listuguj, in the province of Québec. Our objective was to better understand the violence and help-seeking experiences of women from Listuguj, and to initiate actions to improve services offered to Mi’gmaq violence survivors. Based on interviews with violence survivors and workshops with service providers, we created an intervention tool to increase the collaboration among service providers in Listuguj in their actions against violence. This study, the first to focus on the services sought by Mi’gmaq women in Québec, presents another account of the interrelations between interpersonal and structural violence in the lives of Indigenous women. Its partnered approach led to applied results that can be used by Indigenous partners to better meet the needs of violence survivors and their families in their community.